2000
DOI: 10.1073/pnas.97.3.1252
|View full text |Cite
|
Sign up to set email alerts
|

The salicylate-derived mycobactin siderophores of Mycobacterium tuberculosis are essential for growth in macrophages

Abstract: Mycobacterium tuberculosis is an important pathogen of mammals that relies on 2-hydroxyphenyloxazoline-containing siderophore molecules called mycobactins for the acquisition of iron in the restrictive environment of the mammalian macrophage. These compounds have been proposed to be biosynthesized through the action of a cluster of genes that include both nonribosomal peptide synthase and polyketide synthase components. One of these genes encodes a protein, MbtB, that putatively couples activated salicylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
472
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(491 citation statements)
references
References 32 publications
(47 reference statements)
15
472
0
4
Order By: Relevance
“…This suggests that LspA is required for multiplication of M. tuberculosis in early phagosomes. The early phagosome is thought to be a nutrient-restricted environment, which is important in limiting the availability of nutients to phagocytosed bacteria (De Voss et al, 2000;Wagner et al, 2005). Despite some research in this field the key elements critical for adaptation of mycobacteria to this prelysosomal environment are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that LspA is required for multiplication of M. tuberculosis in early phagosomes. The early phagosome is thought to be a nutrient-restricted environment, which is important in limiting the availability of nutients to phagocytosed bacteria (De Voss et al, 2000;Wagner et al, 2005). Despite some research in this field the key elements critical for adaptation of mycobacteria to this prelysosomal environment are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobactin is an intracellular bacterial siderophore which plays a critical role in iron acquisition and transport in M. tuberculosis [50]. To monitor the status of iron starvation of M. tuberculosis within alternatively activated macrophages, expression levels of marker transcripts encoding proteins involved in mycobactin synthesis (mbtB, Rv2383c; mbtJ, Rv2385; mbtI, Rv2386c) as well as the iron storage protein bacterioferritin (bfrB, Rv3841) were determined by qPCR.…”
Section: Alternative Activation Increases Tfr Expression Of Infected mentioning
confidence: 99%
“…In addition, this pathogen also acquires iron from haem 4 ; intracellular M.tb are known to actively recruit host iron carrier proteins transferrin and lactoferrin to the phagosomal compartment [5][6][7][8] . It is reported that carboxymycobactins remove iron from transferrin in the phagosome, while mycobactins present in the bacterial membrane transport this iron into the bacterial cytoplasm 9,10 . Carboxymycobactin also delivers iron by a mycobactinindependent mechanism using the IrtAB transporter 11 .…”
mentioning
confidence: 99%